Electrochemical stability of anodic titanium oxide films grown at potentials higher than 3 V in a simulated physiological solution - Pelaez-Abellan, E.; Rocha-Sousa, L.; Mueller, W.-D.; Guastaldi, Antonio Carlos [UNESP] (Elsevier B.V., 2007)
The cathodic behaviour of oxides formed on titanium electrodes in physiological solutions at potentials between 3 and 5 V (vs. SCE) was studied by cyclic voltammetry. In case of anodic polarization at potentials higher than 3 V (vs. SCE), a cathodic peak at similar to 0.4 V (vs. SCE) appears in the cathodic scan, which could be due to the reduction of unstable peroxides. The results show that this peak depends on the anodic potential and the oxidation time. This behaviour supposedly is due to the formation of unstable titanium peroxides like TiO3 during anodization. Based on repetitive oxidation-reduction processes can be concluded that the created amount of TiO3 inside of the TiO2 surface layer seems to be constant. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: titanium; cyclic voltammetry; potentiostatic polarization; anodic films; oxide coatings